2019
DOI: 10.1093/conphys/coz055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a dynamic rearing environment on development of metabolic phenotypes in age-0 Lake Sturgeon, Acipenser fulvescens

Abstract: Environment–phenotype interactions are the most pronounced during early life stages and can strongly influence metabolism and ultimately ecological fitness. In the present study, we examined the effect of temperature [ambient river temperature (ART) vs ART+2°C], dissolved oxygen (DO; 100% vs 80%) and substrate (presence vs absence) on standard metabolic rate, forced maximum metabolic rate and metabolic scope with Fulton’s condition factor (K), energy density (ED) and critical thermal maximum (CTmax) in age-0 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 83 publications
0
12
1
Order By: Relevance
“…Water temperature regulates metabolic function in fish (Brett 1971; Beitinger and Fitzpatrick 1979; Yoon et al. 2019). Thus, temperature and its resultant effects on metabolism influence the physiological processes that are associated with the stress response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water temperature regulates metabolic function in fish (Brett 1971; Beitinger and Fitzpatrick 1979; Yoon et al. 2019). Thus, temperature and its resultant effects on metabolism influence the physiological processes that are associated with the stress response.…”
Section: Discussionmentioning
confidence: 99%
“…As we were unable to record specific depth or velocity measurements for each angling event, location was included in the model as a categorical variable to characterize variation due to potential habitat-related differences. Finally, water temperature was included in each model, as water temperatures regulate fish metabolism (Brett 1971;Beitinger and Fitzpatrick 1979;Yoon et al 2019). We used a Tobit regression for censured data (i.e., data with upper and lower limits) to test these hypotheses for both glucose and lactate (Tobin 1958).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereafter, 30–34 dpf and 133–134 dpf will be abbreviated as 32 and 133 dpf. Whole body oxygen consumption rate ( ṀO 2 ) was assessed using intermittent flow respirometry (Loligo System, Viborg, Denmark) following previously published protocols (Yoon, Deslauriers, & Anderson, 2019). In larval fish, high developmental demands are known to make it impractical to reliably measure SMR (Chabot et al., 2016; Rosenfeld et al., 2015); thus, we measured routine metabolic rate (RMR) at 32 dpf as a proxy for the minimum energy expenditure to sustain life.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, our study was focused on two populations in Manitoba, which are in the northern range of the species, while the lake sturgeon range is known to extend as far as south as northern Mississippi and Alabama (Bruch et al, 2016). A previous study showed that thermal tolerance of lake sturgeon in Wisconsin, USA, is similar to that of those from Manitoba, possibly due to their closely related thermal regimes (Wilkes, 2011; Yoon, Deslauriers, & Anderson, 2019). However, a future study would benefit from including samples of populations at more southern latitudes and standardized ages, such as 2 weeks following hatch or 2 weeks after transitioning to a bloodworm diet, to address sources of variation in metabolic rate data.…”
Section: Discussionmentioning
confidence: 92%